Intervention of Dr. Juan N Navarro Children's Psychiatric Hospital after the earthquake of September 19, 2017 - Emmanuel Isaías Sarmiento-Hernández; Rosa Elena Ulloa-Flores; Víctor Manuel Ávila-Rodríguez; Jorge Ramírez-Ahuja; Victor Manuel Velázquez-López; Juan Carlos Reséndiz-Aparicio; Maricruz Rodríguez-Arévalo (Instituto Nacional de Salud Pública, 2019)
[Not available]